EXPERT SYSTEM OF DISEASES OF THE FEMALE CHILDBEARING PERIOD USING BAYES THEOREM METHOD - Ananda Sari, Dea; Novriyenni, Novriyenni; Ramadani, Suci (Yayasan Bina Internusa Mabarindo, 2023)
A woman's fertile period is a menstrual cycle in women that occurs once a month. The average fertile period lasts between days 8-19 after the first menstrual period ends. During this fertile period, women will release mature egg cells from the ovaries to the uterus or the so-called ovulation period. There are several menstrual cycles in women, namely the follicular fake menstrual cycle (pre-ovulation) and the luteal phase. If the menstrual period in women is smooth, it is said that it is impossible to have a disease, but in fact there are still diseases in women who have experienced a menstrual period who must get a doctor's treatment as soon as possible.Edward clinic is one of the gynecology clinics that currently serves a variety of health care in pregnant women and complaints in certain areas of women, as well as problems with female fertility. With the development of increasingly sophisticated technology, Edward clinic must be able to follow the development of existing systems in order to make it easier for users to find more complete information by processing patient data and other information. Therefore, the authors want to design an application to assist users in providing services to patients in obtaining more efficient information about the problem of women's fertile period disease, by designing and building a system that will be used in the process to diagnose women's fertile period disease based on symptoms felt by patients using Bayes ' Theorem method, in order to facilitate and shorten the time patients in consultation or further examination. From the results of the study obtained the certainty value of the combination of bayes ' theorem that patients are likely to experience egg follicle disease in women's fertile period with a percentage of 69.50%.